Co-Management in Mangrove Rehabilitation at Langkat Regency - Hamzah, A Hadian Pratama; Anggoro, Sutrisno; Puryono, Sri; Kurniati, Erisa (SCAD Independent, 2021)
Collaboration in the management of mangrove areas is a role for every social element in local government, the community, and the private sector. Co-management is an alternative solution in the form of management that integrates the roles and interests of everyone in the mangrove rehabilitation program. This study aims to analyze the role and level of influence of the interests of each actor in mangrove rehabilitation activities in Langkat Regency. The research method uses descriptive-qualitative data collected from the results of questionnaires, interviews; Field observations are processed in the form described in the description in the tabulation. From the results of this study, the form of joint management in mangrove rehabilitation is at a consultative stage where the government starts to consider local views in the decision-making process, the level of participation of each stakeholder is in a low category, so this Study recommends that the form of participation of each stakeholder can be improved through the form of joint regulations, sustainability programs and systematic work distribution that is disseminated to every implementer of mangrove rehabilitation programs in Langkat District.